Enhancement of power measurement by decimation in 1/f noise - Zali, A. A. B. (Institute of Electrical and Electronics Engineers Inc., 2016)
The assumption of additive white Gaussian noise (AWGN) to model measurement is not valid since many applications such as in RF power measurement the noise is colored with 1/f spectrum characteristics. With this characteristics, the assumption of independently identically distribution (IID) used in signal detection and estimation becomes not valid. The autocorrelation function and power spectrum can be used to characterize both the AWGN and 1/f noise. By the process of decimation, the 1/f noise can be converted to AWGN. Monte Carlo simulation for power measurement in 1/f noise has shown that the decimation reduces the variance by about 11 times. The decimation process has successfully converted real noise signals that consist of 1/f noise and AWGN to AWGN. Thus, the decimation method works for practical applications.